Biomarkers of Docosahexaenoic Acid but Not Arachidonic Acid Reflect Dietary Intakes in Toddlers at Ages 1 and 2 Years Who Are Not Meeting Dietary Recommendations. Issue 3 (22nd November 2019) - Wiedeman, Alejandra M; Dyer, Roger A; McCarthy, Deanna; Yurko-Mauro, Karin; Innis, Sheila M; Devlin, Angela M
ABSTRACT: Background: Long-chain n – 6 and n – 3 PUFAs are important for growth and development. However, little is known about requirements and current dietary intakes of these fatty acids in toddlers. Objectives: This study assessed dietary intakes of n – 6 and n – 3 PUFAs and determined the relation to circulating PUFAs in toddlers at ages 1 and 2 y. Methods: This is a secondary analysis of data from toddlers enrolled in a double-blind randomized controlled trial of arachidonic acid (ARA) and DHA supplementation between ages 1 and 2 y. Dietary intakes of fatty acids were estimated by 3-d food records, and fatty acid composition in plasma total phospholipids, red blood cell phosphatidylethanolamine (PE), and phosphatidylcholine (PC) were assessed by GC at baseline in all subjects ( n = 110; mean age 1.12 y; 64% male) and in the control subjects at 2 y ( n = 43). Results: The dietary intakes of ARA, EPA, and DHA at age 1 y (baseline) were [mean (median)] 36.8 (30.0), 16.0 (0.00), and 31.1 (10.0) mg/d, respectively. Dietary intakes increased to 52.7 (45.0), 35.8 (0.00), and 64.8 (20.0) mg/d, respectively, at age 2 y ( P < 0.05). The predominant dietary source of EPA and DHA was fish/seafood; eggs were an important source of ARA and DHA. Dietary DHA intakes were positively associated with plasma PE and PC DHA ( P < 0.05). No relations between dietary ARA intakes and plasma PE and PC ARA ( P > 0.05) were observed. Conclusions: These findings suggest that most toddlers are not meeting the recommendation for dietary PUFA intakes and that higher dietary DHA intakes are reflected in plasma PE and PC DHA composition. Further work is required to investigate a biomarker for dietary ARA intake. This trial is registered at clinicaltrials.gov as NCT01263912.